دراسة بعض الصفات الكيميائية والميكروبية للبنة المصنعة في المنطقة الساحلية - حرفوش, محسن (Latakia University Journal -Biological Sciences Series, 2019)
هدف هذا البحث إلى تقييم اللبنة المصنعة في المنطقة الساحلية؛ بإجراء بعض التحاليل الكيميائية والميكروبية لـ 30 عينة جمعت من مناطق مختلفة من المنطقة الساحلية خلال الفترة الممتدة بين كلنون الأول 2008 ونيسان 2009. أوضحت النتائج أن جميع العينات مخالفة في نسبة الدهن وكلور الصوديوم للمواصفات القياسية السورية وأن متوسط التعداد الكلي للخمائر والفطور مرتفع في جميع المناطق وقد كان أعلاه في عينات مدينة طرطوس (6.4 X 10 5) وأقله في مدينة جبلة ( 3.6 X 10 5) . كما أظهرت النتائج تباين متوسط التعداد العام لجراثيم الكولي فورم والـ E.coli بين المناطق المختلفة حيث كانت عينات طرطوس خالية منها على حين كان عددها في بقية المناطق متقارباً ومحدودًا نظراً لارتفاع حموضة المنتج, وبلغت نسبة العينات غير المطابقة للمواصفات القياسية السورية 20%. كما تباين متوسط التعداد العام للفطور إذ كان أقل عدد في طرطوس (3.3 X 10 2) وأكثر عدد في اللاذقية (9.2 X 102), وكانت نسبة العينات الملوثة بالفطور 60% من المجموع الكلي للعينات, كما دلت نتائج تشخيص الفطور على وجود ثمانية أنواع كان الأكثر تردداً فطر Aspergillus versicolor (40%). أظهرت الاختبارات المتعلقة بكشف الغش وأنواعه أن نحو 26% من العينات الكلية قد تعرضت للغش وأن غالبية حالات الغش كانت بإضافة النشا. The purpose of this research was to evaluate the quality of labneh (concentrated yoghurt) made in the Syrian coastal region by determining some chemical and microbial properties of 30 samples, collected from different locations between December 2008 and April 2009 . The results showed that all labneh samples did not comply with the Syrian standards regard to fat and NaCl. Average total counts of yeasts and molds were high in all samples and ranged between (3.6 X 105) in Jableh samples and ( 6.4 X 105) in Tartous samples. As far as the coliform group and E.coli are concerned, Tartous samples were void of them, but 20% of the total samples were contaminated and hence, did not comply with the Syrian standard. The average total count, however, was similar and limited due to the high acidity of labneh. There were significant variations in the average total counts of molds in labneh between locations. Tartous city showed the lowest number (3.3 X 102) , whereas Lattakia city was the highest (9.2 X 105). Sixty percent of the samples were contaminated with molds. Results of molds diagnosis revealed that there were eight species of mold with Aspergillus versicolor being the most dominant (40%). The tests indicated that 26% of the samples were adulterated mostly with starch.